The Influence of Nutritional Status, Physical Fitness, and Learning Motivation on Learning Outcomes in Physical Education, Sport and Health - Icuk Sugiarto; Tjung Hauw sin; Gusril; Aldo Naza Putra (UNIB Press, 2023)
The aim of the study was to see the effect of nutritional status, physical fitness, and learning motivation on PJOK learning outcomes. This type of research is path analysis. The research population is students of SMPN 1 Tungkal Ulu. Sampling used purposive sampling, with a total of 30 female students. The research instrument used the Body Mass Index test, the Fitness Test for Indonesian Students, the Likert Questionnaire, and the results of the PJOK report cards. The results showed that: (1) There is a direct influence of nutritional status on students' PJOK learning outcomes (2) There is a direct influence of physical fitness on students' PJOK learning outcomes (3) There is a direct influence of learning motivation on students' PJOK learning outcomes (4) There is an indirect influence of nutritional status on students' results learning PJOK through students' learning motivation (5) There is an indirect influence of physical fitness on PJOK learning outcomes through students' learning motivation (6) There is an indirect influence of nutritional status on PJOK learning outcomes through students' physical fitness.